Accessibility of Interactive Instructional Media in The Delivery of Distance Education in South-East Nigeria - Onovo, Joseph Sunday (West African Journal of Open and Flexible Learning, 2017)
The purpose of the study was to determine the extent to which interactive instructional media are accessible and actually utilized in the delivery of distance Education programmes. The study was carried out in the south East Nigeria. A survey Research Design was adopted for the study. A research question and two hypotheses guided the study. 47,084 students of the National Open University of Nigeria (NOUN) and National Teachers Institute (NTI) Distance Education programmes in Abia and Enugu State study centres constituted the population for the study. With a stratified random sampling technique, a sample size of 393 distance learners from the NOUN and NTI centres were selected and studied. A researcher designed questionnaire, “Learners perceptions of Accessibility of Interactive Instructional Media Questionnaire” was used for data collection. The Instrument was validated by three experts; two in curriculum and instruction and one in measurement and Evaluation. The reliability co-efficient of the instrument was 0.76 obtained through Cronbach Alpha Method. The research question was tested using mean and standard deviations while the hypotheses were tested using t-test statistics. The data analysis revealed nonaccessibility and under-utilization of the studied interactive instructional media. There was no significant difference between the mean ratings of the Abia and Enugu study centre students’ responses, but there was a significant difference between the mean ratings of the Noun and NTI students’ responses. Based on the findings, it was recommended among others, that awareness, knowledge and skills acquisition training programmes on the accessibility and utilization of interactive instructional media should be severally organized to enable distance learning students and facilitators exploit the immense benefits and opportunities being offered by the current advancement in information and communication Technology. Résumé : Le but de cette recherche était de déterminer dans quelle mesure les médias éducatifs interactifs sont accessibles et effectivement utilisés dans l'enseignement à distance. La recherche a été menée dans la région sud-est du Nigeria. Un plan de recherche par sondage a été adopté. Une question de recherche et deux hypothèses ont guidé la recherche. 47, 084 étudiants des programmes d'enseignement à distance de l'Université nationale de l’enseignement à distance du Nigéria (NOUN) et du National Teachers Institute (NTI) dans les centres d'études aux états d'Enugu et d’Abia constituaient la population utilisée par la recherche. Grâce à une technique d'échantillonnage aléatoire stratifié, un échantillon de 393 apprenants à distance des centres NOUN et NTI a été sélectionné et étudié. Un questionnaire a été utilisé pour la collecte de données. L'instrument a été validé par trois experts : deux en matière de programmes et d'enseignement et un en matière de mesure et d'évaluation. Le coefficient de fiabilité de l'instrument était de 0,76 obtenu par la méthode alpha de Cronbach. La question de recherche a été vérifiée à l'aide des écarts moyens et des écarts-types, tandis que les hypothèses ont été vérifiées à l'aide des statistiques du test - T. L'analyse des données a révélé la non-accessibilité et la sous-utilisation des médias pédagogiques interactifs étudiés. Il n'y avait pas de différence significative entre les cotes moyennes des réponses des élèves des centres d'étude Abia et Enugu, mais il y avait une différence significative entre les cotes moyennes des réponses des élèves Noun et NTI. Sur la base de ces conclusions, il a été recommandé, entre autres, que des programmes de formation à la sensibilisation, aux connaissances et à l'acquisition de compétences sur l'accessibilité et l'utilisation des médias pédagogiques interactifs soient organisés séparément pour permettre aux étudiants et aux facilitateurs de l'enseignement à distance d'exploiter les immenses avantages et possibilités offerts par le progrès actuel des technologies de l'information et des communications.